Pelatihan Metode Riset Konsep Layanan Rumah Sakit Syariah Bagi Pegawai RSUI Klaten - Winarno Heru Murjito; Hartanto; Hersulastuti; Syska Lady Sulistyowatie; Tasari (Jurnal Masyarakat Indonesia (Jumas), 2025)
This Community Service Activity is an investigation of scientific activities related to problems in the field of science based on sharia-based health services. The purpose of the research training activity for education and training for employees at three Islamic General Hospitals (RSUI) is to train, answer and practice learning comprehensive sharia concepts based on scientific methods. This community service develops science by conducting observations, identifying problems, formulating problems, proposing frameworks, formulating hypotheses, collecting data, analyzing data, interpreting data and drawing conclusions. A good mindset is needed to carry out research, namely a logical and empirical mindset. The results of the activity obtained positive changes in the emergence of changes in thinking before and after training, increasing the education and training employees’ ability in practicing research activities, data processing, and increasing the ability to interpret research outputs